Optimalisasi Teknologi Hydroponik Sistem DFT Sebagai Sumber Pangan Sehat Di Kelurahan Panji Sari - Hasyim; Raden Deden Saputra; Raden Dinda Septyareni Diyasmin; Nova Sri Widiana; Nyoman Bangbang Pradnya Wira Brata; Bahrul Sundusi Adnan; Abdul Malik Ashri Wirajagat; Irma Watianggrianingsi; Raudatul Jannah; Baiq Ega Zulqaidah Putri; Mariani (Universitas Mataram, 2026)
The Real Work Lecture (KKN) work program aims to implement the Deep Flow Technique (DFT) hydroponic planting system as a form of community service in limited land use and increasing household food security. The DFT system was chosen because it is easy to implement, efficient in water and nutrient use, and has relatively simple maintenance. The implementation of the program includes the creation of hydroponic installations, vegetable planting, as well as education and assistance to the community regarding cultivation techniques and maintenance of hydroponic plants. The results of the activity show that there is an increase in community knowledge and skills in cultivating vegetables without soil, so that this program is expected to be an alternative to sustainable agriculture that can be developed in the community.